Practice pattern variability in the management of acute severe colitis: a UK provider survey. Issue 4 (17th August 2019) - Sebastian, Shaji; Lisle, Jessica; Subramanian, Sreedhar; Dhar, Anjan; Shenoy, Achut; Limdi, Jimmy; Butterworth, Jeffrey; Allen, Patrick B; Samuel, Sunil; Moran, Gordon; Shenderey, Richard; Parkes, Gareth; et al.
Abstract : Introduction: Lack of comparative trial data on dosing regimens of infliximab in patients with acute severe ulcerative colitis (ASUC) failing intravenous corticosteroids has resulted in variability of rescue regimes in ASUC with potential impact on clinical outcomes. We aimed to evaluate practice variability and physician perspectives in decision-making with rescue therapy. Methodology: An internet-based survey of members of the inflammatory bowel disease (IBD) section of the British Society of Gastroenterology was conducted. The survey evaluated provider characteristics and general practice in the setting of ASUC, followed by a vignette with linked questions. Results: The response rate of the survey was 31% (209/682 IBD section members). 134 (78%) reported they would use standard infliximab dose (5 mg/kg) while 37 (22%) favoured a higher front-loading dose of 10 mg/kg citing low albumin, high C-reactive protein as their reason for their preference. IBD specialists chose the higher front-loading dose more often compared with other gastroenterologists (p=0.01) In the specific case vignette, accelerated induction (AI) was favoured by 51% of the respondents while 25% used the standard induction regime and 19% favoured colectomy. IBD specialists more often favoured AI compared with other gastroenterologists (p=0.03) with the main reason being presence of predictors of low infliximab levels (74%). The reasons cited for favouring standard induction (n=57) included lack of evidence for AI (18), their usual practice (11), unlicensed regime (7), and safety concerns (4). Conclusions: There are significant variations in practice in the use of infliximab rescue therapies with an urgent need for development of care pathways to standardise practice.